Geomagnetic control of polar mesosphere summer echoes. - Bremer, J.; Hansen, T.L.; Hoffmann, P. (European Geophysical Society, 2000)
Using observations with the ALOMAR SOUSY radar near Andenes (69.3°N, 16.0°E) from 1994 until 1997 polar mesosphere summer echoes (PMSE) have been investigated in dependence on geomagnetic K indices derived at the Auroral Observa- tory Tromsù (69.66°N, 18.94°E). During night-time and morning hours a significant correlation between the signal-to-noise ratio (SNR) of the radar results and the geomagnetic K indices could be detected with a maxi- mum correlation near midnight. The correlation be- comes markedly smaller in the afternoon and early evening hours with a minimum near 17 UT. This diurnal variation is in reasonable agreement with riometer absorption at Ivalo (68.55°N, 27.28°E) and can be explained by the diurnal variation of ionization due to precipitating high energetic particles. Therefore, a part of the diurnal PMSE variation is caused by this particle precipitation. The variability of the solar EUV varia- tion, however, has no significant influence on the PMSE during the observation period.